BENTUK-BENTUK PERMINTAAN SOPAN DALAM BAHASA INGGRIS DAN BAHASA TONTEMBOAN (SUATU ANALISIS KONTRASTIF) - Lumenta, Elkana Sari; Rattu, Jultje A.J.; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT            This research is entitled ?Forms of Polite Requet in English and Tontemboan Language ( A Contrastive Analysis). The aim  of this research is to identify, classify, analyze and to contrast polite utterance in English and Tontemboan Language. In this research, the writer uses descriptive method. The English data were collected from English Grammar Book, website, film and some previous skripsi, while the data of Tontemboan language were collected by doing interview to the native speaker in Raanan Baru village. In this research, the writer uses the theory of Leech (1983)  in analyzing the data and the theory of Lado ( 1971) in contrasting both languages to find out their similarities and differences. The result of this research shows that English and Tontemboan language has similarities and differences. In terms of similarities, each language has six maxims of politeness that are used to avoid estrangement during conversation. The differences between these two languages can be seen in the sentence structure. In English the subject is always at the beginning of the sentence for example I go to school, whereas in Tontemboan the subject is usually at the end of the sentence for example mange am pasar  yaku. In addition, the difference between these languages is glotal or emphasis in the pronunciation of words in English is not written, whereas in Tontemboan language is always written. Keywords : Forms of Polite Request, English and Tontemboan Language,  Contrastive Analysis.